Agility and not change of direction speed discriminates competitive level in young soccer players (The Journal of Strength and Conditioning Research, 2025)
This study aimed to examine the discriminant ability of agility and change of direction speed (CODS) among young soccer players. Eighty-seven male soccer players (U-15 age group) were analyzed and grouped based on competitive level as nonelite, subelite, and elite players. Anthropometry, maturity offset, agility (perception-decision time, and movement response time), and CODS were assessed. Linear discriminant analysis (LDA) was applied to obtain the standardized coefficients of each variable in the model and the accuracy of the model comparing the predicted with the true group. Aiming to describe the discriminant ability of CODS and agility, all LDA models also included subjects age, maturity offset, and training age. Standard discriminant function (SDF) revealed that CODS (SDF = -0.012) or perception-decision (SDF = -0.380) time has a reduced discriminatory ability compared with age and maturity offset. When considering all variables, movement response time (SDF = -0.726) and maturity offset (SDF = 0.595) contributed the most to the discriminant ability of the models (75% accuracy). Moreover, movement response time correctly classified elite (accuracy >84%) compared with subelite and nonelite players. Our results indicate that agility tests with specific stimuli are better than CODS tests at distinguishing young soccer players of different competitive levels, even when considering the effects of age, maturity status, and training age. In addition, the movement response time emerges as the primary factor influencing agility performance in young athletes. Monitoring these qualities may help coaches in the talent identification and development program.